2020
DOI: 10.1121/10.0000578
|View full text |Cite
|
Sign up to set email alerts
|

Offline and online processing of acoustic cues to word stress in Papuan Malay

Abstract: The present study investigates to what extent acoustic cues to word stress facilitate both offline and online word processing in Papuan Malay. Previous production research has shown acoustic evidence for word-stress patterns in this language, counter to earlier predictions. A discussion of the literature on word stress perception and word stress in Papuan Malay is provided and complemented with reports of three word recognition tasks. The first two presented sequences of acoustically manipulated syllable dyads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…It was found that vowel reduction in Papuan Malay is among the strongest acoustic correlates of word stress [23]. Perception experiments using manipulated stimuli showed that Papuan Malay listeners were mainly sensitive for the irregular penultimate stress pattern [25]. Crucially, in [25] the effect of vowel reduction on stress perception was not tested.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that vowel reduction in Papuan Malay is among the strongest acoustic correlates of word stress [23]. Perception experiments using manipulated stimuli showed that Papuan Malay listeners were mainly sensitive for the irregular penultimate stress pattern [25]. Crucially, in [25] the effect of vowel reduction on stress perception was not tested.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the number of embedded words, a list of phonetically transcribed Papuan Malay words was used (Appendix A in [25]). The list consisted of a written lexeme, a phonetic transcription, a word class label and an English gloss.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations